2018
DOI: 10.1371/journal.pone.0191999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi and soil nutrient addition on the growth of Phragmites australis under different drying-rewetting cycles

Abstract: The frequency of soil drying–rewetting cycles is predicted to increase under future global climate change, and arbuscular mycorrhizal fungi (AMF) are symbiotic with most plants. However, it remains unknown how AMF affect plant growth under different frequencies of soil drying–rewetting cycles. We subjected a clonal wetland plant Phragmites australis to three frequencies of drying-rewetting cycles (1, 2, or 4 cycles), two nutrient treatments (with or without), and two AMF treatments (with or without) for 64 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Besides shoot and root weight, the leaf area is also important from the agronomical point of view and is influenced by various nutrient supplies (Taranet et al, 2017) or/and mycorrhizal inoculation (Liang et al, 2018). AMF had positive influence on leaf area of E. prostrata, a finding that is similar with the results of Birhane et al (2012), who reported enhancing leaf area, biomass, and stomatal conductance by Boswellia papyrifera inoculation with AMF.…”
Section: Discussionsupporting
confidence: 71%
“…Besides shoot and root weight, the leaf area is also important from the agronomical point of view and is influenced by various nutrient supplies (Taranet et al, 2017) or/and mycorrhizal inoculation (Liang et al, 2018). AMF had positive influence on leaf area of E. prostrata, a finding that is similar with the results of Birhane et al (2012), who reported enhancing leaf area, biomass, and stomatal conductance by Boswellia papyrifera inoculation with AMF.…”
Section: Discussionsupporting
confidence: 71%
“…This result was hypothetically unexpected (Fig. 2C), but some previous studies demonstrated that P fertilization did not reduce AMF colonization in the host roots [32,33]. Perhaps, the alteration of AMF colonization might be undetectable within the short-term.…”
Section: Discussionmentioning
confidence: 68%
“…They can cooperate with one another (Stuefer et al 1996;Alpert & Stuefer 1997;Bittebiere et al 2020). Additionally, networks of many clonal plants are interconnected with networks of AMF and other microorganisms (e.g., Streitwolf-Engel et al 1997;Streitwolf-Engel et al 2000;Liang et al 2018;Vannier et al 2018). A developing network expands and takes up an increasing amount of space.…”
Section: Discussionmentioning
confidence: 99%